Pengaruh Modifikasi Permukaan Karbon Aktif Sekam Padi Menggunakan HNO3 terhadap Kapasitansi Spesifik dengan Elektrolit HCl, KOH, dan KCl - Azis, Nuritasari; Febrianti, Triana; Ta’bi, Widi Aprilia (CV. Green Publisher Indonesia, 2026)
Biomass-based activated carbon has potential as an electrode material in energy storage systems because it is renewable and environmentally friendly, but its performance is still dominated by the Electric Double Layer Capacitance (EDLC) mechanism. This study aims to examine the effect of surface modification of rice husk activated carbon using HNO3 on the specific capacitance of carbon paste electrodes in various types of electrolytes. Activated carbon was synthesized through the stages of carbonization, silica extraction, chemical activation using H3PO4, and surface modification using HNO3. Material characterization was carried out using X-Ray Fluorescence (XRF), Scanning Electron Microscope (SEM), Surface Area and Porosity with the Brunauer-Emmett-Teller (BET) method, Fourier Transform Infra-Red (FTIR), and Boehm titration. The electrochemical performance of the electrode was evaluated using the cyclic voltammetry method with HCl, KOH, and KCl electrolytes at a concentration of 0.5 M. FTIR and Boehm titration results showed an increase in the number of oxygen groups on the surface of activated carbon after modification. Electrochemical testing showed that the type of electrolyte affected the specific capacitance value, with KOH electrolyte producing the highest specific capacitance of 31.5094 mF/g on the modified activated carbon electrode (KAEM). This increase in capacitance was attributed to the contribution of the pseudocapacitance mechanism due to the interaction of oxygen functional groups on the surface of activated carbon with OH- ions, while in HCl and KCl electrolytes the charge storage mechanism was dominated by electric double layer capacitance.